Productivity Of Arabica Coffee Varieties Under Pine Trees - Wahyuni, Dwi; Aditya Sarif Hidayat; Ina Darliana (Greenation International Journal of Tourism and Management, 2023)
The Community Forest Management (PHBM) program has attempted to increase soil productivity in forest areas by planting coffee under trees. The planting system used by Perhutani under PHBM is intercropping. This planting pattern aims to optimize the potential of land use for community welfare. This study aims to determine the Arabica coffee variety (Coffea arabica L.) with the highest productivity among pine stands at LMDH Campaka Bentang, Bandung Regency. The method used was experimental, with a completely randomized design (CRD) of five treatments with eight repetitions. The study was limited to five varieties of coffee plants grown by farmers with uniform coffee care or maintenance at the same planting date and in one plot. The results showed that the Ateng super variety had the highest average fruit weight per 100 seeds, the highest number of fruits, and the highest number of productive branches per tree, while the Ateng variety had the lowest value. The longest productive branch length per tree parameter was found in the Typica variety and the lowest in the Ateng variety. Further test results using Duncan's test with a 5% confidence level showed that the Ateng super variety had the highest value in the tested parameters compared to the other four varieties, while the lowest value was found in the Ateng variety.